MRI Detection of Carotid Intraplaque Hemorrhage and Postintervention Cognition - Culleton, S.; Baradaran, H.; Kim, S.-E.; Stoddard, G.; Roberts, J.; Treiman, G.; Parker, D.; Duff, K.; McNally, J.S. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Cognitive improvement has been reported after carotid revascularization and attributed to treating stenosis and correcting hypoperfusion. This study investigated the effect of carotid intraplaque hemorrhage on postintervention cognition.MATERIALS AND METHODS: In this institutional review board–approved single-center study, consecutive patients scheduled for carotid surgery were recruited for preoperative carotid MR imaging (MPRAGE) and pre- and postintervention cognitive testing using the Repeatable Battery for the Assessment of Neuropsychological Status. Pre- and postintervention scores were compared using t tests and multivariable linear regression.RESULTS: Twenty-three participants were included, with endarterectomy performed in 20 (87%) and angioplasty/stent placement, in 3 (13%). Overall, statistically significant improvements occurred in the pre- versus postintervention mean Total Scale score (92.1 [SD, 15.5] versus 96.1 [SD, 15.8], P = .04), immediate memory index (89.4 [SD, 18.2] versus 97.7 [SD, 14.9], P < .001), and verbal index (96.1 [SD, 14.1] versus 103.0 [SD, 12.0], P = .002). Intraplaque hemorrhage (+) participants (n = 11) had no significant improvement in any category, and the attention index significantly decreased (99.4 [SD, 18.0] versus 93.5 [SD, 19.4], P = .045). Intraplaque hemorrhage (−) participants (n = 12) significantly improved in the Total Scale score (86.4 [SD, 11.8] versus 95.5 [SD, 12.4], P = .004), immediate memory index (82.3 [SD, 14.6] versus 96.2 [SD, 14.1], P = .002), delayed memory index (94.3 [SD, 14.9] versus 102.4 [SD, 8.0], P = .03), and verbal index (94.3 [SD, 13.2] versus 101.5 [SD, 107.4], P = .009). Postintervention minus preintervention scores for intraplaque hemorrhage (+) versus (−) groups showed statistically significant differences in the Total Scale score (−0.4 [SD, 6.8] versus 8.0 [SD, 8.5], P = .02), attention index (−5.9 [SD, 8.5] versus 4.3 [SD, 11.9], P = .03), and immediate memory index (4.2 [SD, 6.7] versus 12.2 [SD, 10.2], P = .04).CONCLUSIONS: Cognitive improvement was observed after carotid intervention, and this was attributable to intraplaque hemorrhage (−) plaque. MR imaging detection of intraplaque hemorrhage status may be an important determinant of cognitive change after intervention.ACAanterior cerebral arteryBMIbody mass indexIPHintraplaque hemorrhagePCAposterior cerebral arteryRBANSRepeatable Battery for the Assessment of Neuropsychological Status